Analysis of caloric intake and its relationship with body composition in university students - Parraca, J.A. (2018)
Thirty-one older people (age 70,2±6,3 years) were randomly assigned to an experimental group (n=16), performing 16 weeks, 2 weekly sessions of 30 min of exercise with warm up (5 min bycicle and 5 min 4 set of exercises) 30 sec x 4 sets of whole body vibration (WBV) with 60 sec of rest between sets; or to a control group (n=15). Maximal isokinetic strength was measured at 60º/s in the knee extensors and flexors in concentric action. Dynamic balance was evaluated using The Timed up and Go Test (Rikli & Jones, 1999). Fueron observadas diferencias significativas entre hombres y mujeres en Kcal (male 22 vs. female 2026±3; p=0,044). After 16 weeks of WBV exercise significant improvements occurred in concentric extensors strength at 60º/s and in dynamic postural balance (Table 1). Multivariate regression analyses indicated that gains in concentric knee extensors strength predicted improvements in postural balance |F (2, 17) = 17,410; R2 = 0,351; p = 0.026)|. A WBV exercise produced relevant gains in dynamic postural balance (≈16%) and muscle strength at low velocities of movements in extensors (≈17%), some of which predicted improvements (≈35%) in dynamic balance.